Novel Treatments of Adult T Cell Leukemia Lymphoma - El Hajj, Hiba; Tsukasaki, Kunihiro; Cheminant, Morgane; Bazarbachi, Ali; Watanabe, Toshiki; Hermine, Olivier (Frontiers in Microbiology, 2020)
Adult T cell leukemia-lymphoma (ATL) is an aggressive malignancy secondary to chronic infection with the human T cell leukemia virus type I (HTLV-I) retrovirus. ATL carries a dismal prognosis. ATL classifies into four subtypes (acute, lymphoma, chronic, and smoldering) which display different clinical features, prognosis and response to therapy, hence requiring different clinical management. Smoldering and chronic subtypes respond well to antiretroviral therapy using the combination of zidovudine (AZT) and interferon-alpha (IFN) with a significant prolongation of survival. Conversely, the watch and wait strategy or chemotherapy for these indolent subtypes allies with a poor long-term outcome. Acute ATL is associated with chemo-resistance and dismal prognosis. Lymphoma subtypes respond better to intensive chemotherapy but survival remains poor. Allogeneic hematopoietic stem cell transplantation (HSCT) results in long-term survival in roughly one third of transplanted patients but only a small percentage of patients can make it to transplant. Overall, current treatments of aggressive ATL are not satisfactory. Prognosis of refractory or relapsed patients is dismal with some encouraging results when using lenalidomide or mogamulizumab. To overcome resistance and prevent relapse, preclinical or pilot clinical studies using targeted therapies such as arsenic/IFN, monoclonal antibodies, epigenetic therapies are promising but warrant further clinical investigation. Anti-ATL vaccines including Tax peptide-pulsed dendritic cells, induced Tax-specific CTL responses in ATL patients. Finally, based on the progress in understanding the pathophysiology of ATL, and the risk-adapted treatment approaches to different ATL subtypes, treatment strategies of ATL should take into account the host immune responses and the host microenvironment including HTLV-1 infected non-malignant cells. Herein, we will provide a summary of novel treatments of ATL in vitro, in vivo, and in early clinical trials.